Voices of excellence: elite athletes' perspectives on support gaps, suggestions for improvement and their emergence - Griesinger, Alex Nico; Ehnold, Peter; Zetzsche, Robert; Schlesinger, Torsten (Frontiers in Sports and Active Living, 2025)
Elite athlete support is an area of elite sport development currently undergoing significant transformation, driven by athletes' demands for greater influence over the conditions under which they pursue their risky careers. Considering its potential to offer nations a competitive advantage, the field is continuously evolving and attracting growing strategic interest. The aim of the study is to examine elite athletes' unmet support needs, suggestions for improvement and their emergence to generate practically relevant insights and foster scientific knowledge. A qualitative design was applied, combining semi-structured interviews and biographical mapping with 23 German Olympic and Paralympic athletes from 12 sports. The data were analysed using content analysis and case-specific biographical-narrative reconstruction. Support needs and suggestions for improvement were individual and closely tied to athletes' life contexts, with most relating to training, dual career, financial and material support. Across support categories, the effectiveness of services depends on delivery quality as well as contextual factors such as information availability, communication and timing. In addition, athletes emphasise the need for interconnecting support measures and for earlier, more responsive support systems that adapt to changing circumstances. In this context, athletes highlight the central role of coaches in facilitating and ensuring support effectiveness. This study enriches holistic athlete support research by offering elite athlete-centred insights into the prevalence and emergence of support needs across careers. By integrating cross-case comparison with narrative depth, it delivers a rare blend of detailed and actionable insights from Olympic and Paralympic elite athletes that can inform more effective support systems in elite sport.